Brucella abortus BspJ Is a Nucleomodulin That Inhibits Macrophage Apoptosis and Promotes Intracellular Survival of Brucella - Ma, Zhongchen; Li, Ruirui; Hu, Ruirui; Deng, Xiaoyu; Xu, Yimei; Zheng, Wei; Yi, Jihai; Wang, Yong; Chen, Chuangfu (Frontiers in Microbiology, 2020)
To date, a variety of Brucella effector proteins have been found to mediate host cell secretion, autophagy, inflammation, and other signal pathways, but nuclear effector proteins have not yet been reported. We identified the first Brucella nucleomodulin, BspJ, and we screened out the BspJ interaction host proteins NME/NM23 nucleoside diphosphate kinase 2 (NME2) and creatine kinase B (CKB) through yeast two-hybrid and co-immunoprecipitation assays. These proteins are related to the host cell energy synthesis, metabolism, and apoptosis pathways. Brucella nucleomodulin BspJ will decrease the expression level of NME2 and CKB. In addition, BspJ gene deletion strains promoted the apoptosis of macrophages and reduced the intracellular survival of Brucella in host cells. In short, we found nucleomodulin BspJ may directly or indirectly regulate host cell apoptosis through the interaction with NME2 and CKB by mediating energy metabolism pathways in response to the intracellular circulation of Brucella infection, but the mechanism needs further study.